Comparison of Ice-shelf Creep Flow Simulations with Ice-front Motion of Filchner-Ronne Ice Shelf, Antarctica, Detected by SAR Interferometry - Hulbe, C. L.; Rignot, E.; MacAyeal, D. R. (2004)
Comparison between numerical model ice-shelf flow simulations and synthetic aperture radar (SAR) interferograms is used to study the dynamics at the Hemmen Ice Rise (HIR) and Lassiter Coast (LC) corners of the iceberg-calving front of the Filchner-Ronne Ice Shelf (FRIS).